Sistem Pendukung Keputusan Penyeleksian Colour Guard Pada Marching Band Ginada Dengan Menggunakan Metode Vikor Dan Borda - Nurjannah; Dito Putro Utomo (Yayasan Kita Menulis, 2020)
Decision support system for selecting color guard with VIKOR and Borda methods. It has been made as a tool to select color guard at the Sei Rampah High School. The criteria used in the decision support system for color guard selection are: height, weight, agility, stamina, and body language. Color guard selection activities are a routine activity every year, so GINADA marching band coach Sei Rampah hereby selects to select permanent members in the marching band. Decision Support System in an organization can be seen as important in supporting the smooth running of activities and achieving an organizational goal. SPK can come in various forms, ranging from simple forms of data processing to complex application forms, and can also be used to accelerate and improve the quality of the decision-making process in the organization.